Assessment of the risk of musculoskeletal adverse events associated with fluoroquinolone use in children: A meta-analysis. Issue 34 (21st August 2020) - Wang, Ji-gan; Cui, Hai-Rong; Hu, Yi-sen; Tang, Hua-Bo
Abstract: Background: The use of fluoroquinolone antibiotics has been restricted in children because of their potential to cause adverse musculoskeletal events. This study was performed to systematically evaluate whether there is a difference between fluoroquinolone and non-fluoroquinolone antibiotics in terms of their associated risk of adverse musculoskeletal events in children. Methods: Cochrane Library, Embase, and PubMed databases were used to retrieve studies related to fluoroquinolone and non-fluoroquinolone-induced musculoskeletal adverse events in children. A meta-analysis was performed using Stata 11. Results: A total of 10 studies were included in the analysis. The combined results showed that there was no statistical difference between fluoroquinolone and non-fluoroquinolone groups in terms of musculoskeletal adverse events in children (risk ratio = 1.145, 95% confidence interval = 0.974 – 1.345, P = .101). Subgroup analysis was performed using a random-effects model. Here, the effects on the trovafloxacin and levofloxacin groups were significantly different from that of the control group. However, musculoskeletal adverse events due to either drug was not reported after long-term follow-up. Conclusions: The results showed that fluoroquinolone and non-fluoroquinolone antibiotics were not different in terms of their ability to cause musculoskeletal adverse events in children. For this reason, fluoroquinolone antibiotics can be used in children as appropriate. PROSPERO registration number: CRD42019133900 Abstract : Supplemental Digital Content is available in the text